The Ability of Basalt to Leach Nutrients and Support Growth of Cupriavidus metallidurans CH34 Depends on Basalt Composition and Element Release. Issue 5 (28th May 2018) - Byloos, Bo; Maan, Harsh; Van Houdt, Rob; Boon, Nico; Leys, Natalie
ABSTRACT: The influence of different rock mineralogical compositions on element leaching and bio-weathering processes is poorly understood. Here, the role of basalt composition on nutrient leaching (calcium, iron, phosphorus or magnesium) and subsequent support of Cupriavidus metallidurans CH34 growth was evaluated. Seven different basalts were examined. In iron-limiting media, growth could be restored for all basalts tested, while only two basalts could restore growth in magnesium-limiting medium. Only for magnesium growth complementation was correlated with the composition of the basalts tested. Our results showed that basalt composition can affect leaching and availability of different elements, in turn, affecting bacterial growth.